Exposure of Cyprinus carpio var. larvae to PVC microplastics reveals significant immunological alterations and irreversible histological organ damage - Liu, Xinya; Liang, Chaonan; Zhou, Miao; Chang, Zhongjie; Li, Li (Ecotoxicology and environmental safety, 2023)
Microplastics have become pervasive in ambient aquatic ecosystems over the last decade and are currently a serious global scale concern. To evaluate the potential toxic effects of PVC (polyvinyl chloride) microplastics on the immune functions of freshwater fish, this study undertook a conducted chronic 60-day dietary exposure experiment with Cyprinus carpio var. larvae. We exposed the fish to four microplastic treatments of different concentrations (food rationed diets): no-plastic (control), 10%, 20% and 30%. At the end of the experimental period the impacts of microplastics on the histology, biochemistry, ROS (reactive oxygen species) levels and gene transcription of immune organs were investigated. The results revealed that PVC microplastics induced cytoplasmic vacuolation in the liver, damaged villi in the intestine, inflammatory cell infiltration, hemosiderosis and vacuolar degeneration in the spleen, glomeruli tuft shrinkage and aggregation of melanin macrophage cells in the kidney. Moreover, following PVC microplastics exposure, ROS levels in the liver and protein levels of pro-inflammatory cytokines including IL-6, IL-8, and TNFα in the liver and serum were increased. Furthermore, modifications in the activities of non-specific immunoenzyme ACP (Acid phosphatase), AKP (alkaline phosphatase), LZM (lysozyme), and expression levels of a range of immune-related genes were observed. Using various techniques at the histological, biochemical and molecular levels, our findings demonstrated the effects of PVC microplastics on changes and imbalances in the immune status of carp. The results of this study provide basic toxicological data toward elucidating and quantifying the impacts of microplastics immunotoxicity on aquatic organisms. [Display omitted] •PVC microplastics caused tissue damage in livers, intestines, spleens and kidneys of carp larvae.•Carp larvae exposed to PVC microplastics show increased protein levels of cytokines.•PVC-exposure altered immunoenzyme activities and immune-related gene expression.•Increase in ROS levels is observed in carp larvae exposed to PVC microplastics.